Answer:
<em>y = - cos ( </em>
<em> x + </em>
<em> ) </em>
Step-by-step explanation:
y = A cos ( Bx + C) + D
Vertical shift D = 0
A = - 1
Compression / Stretching B
Period of given function is
Period of cos x is 2π
=
⇒ B =
Horizontal shift is C ÷ B
Horizontal shift of given function is
= C ÷
⇒ C =
So, the equation of given function is
<em>y = - cos ( </em>
<em> x + </em>
<em> ) </em>
Answer:
option 2,5 are correct
Step-by-step explanation:
mark me as brainliest ❤️
Answer:
I think it would be X x 5 = Y
Step-by-step explanation:
Answer:
4 * (x-9)=-30
not sure if u want it solved but if u do its x=6/4
Step-by-step explanation:
Ans: About 2.30
-15 x 3.16 / 9 = x sqrt
-15 x 3.16 = - 47.4
-47.4 / 9 = -5.27
-5.27 sqrt = About 2.30
Hope this helped :)